2006
DOI: 10.5713/ajas.2006.1234
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Genetic Variability in Two North Indian Buffalo Breeds Using Random Amplified Polymorphic DNA (RAPD) Markers

Abstract: Murrah and NiliRavi are the important North Indian buffalo breeds occupying the prominent position of being the highest milk producers. These breeds are more or less similar at morphological as well as physiological levels. The technique of RAPD-PCR was applied in the present study to identify a battery of suitable random primers to detect genetic polymorphism, elucidation of the genetic structure and rapid assessment of the differences in the genetic composition of these two breeds. A total of 50 random prime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
2
1
Order By: Relevance
“…The percentage of the primers screened that were amplification in the present study was much higher than that reported by Sodhi et al (2006). Of the 50 primers they used to screen two buffalo breeds, only 26 generated reproducible banding patterns.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The percentage of the primers screened that were amplification in the present study was much higher than that reported by Sodhi et al (2006). Of the 50 primers they used to screen two buffalo breeds, only 26 generated reproducible banding patterns.…”
Section: Discussioncontrasting
confidence: 57%
“…It is difficult to find monomorphic, unique RAPD markers for species, breed or population distinction and thus identification due to its highly polymorphic nature. Sodhi et al (2006) found two RAPD markers that were present in the NiliRavi buffalo breed but absent in the Murrah buffalo, however, these were polymorphic. Similarly, in the study comparing catla (Catla catla) from three major river systems, Islam et al (2005) found two RAPD markers unique to the Halda river population and one RAPD marker unique to the Padma river.…”
Section: Discussionmentioning
confidence: 90%
“…They consist of strings of tandem repeats of short motifs ranging from mono to penta nucleotides with variability in the number of repeats (Litt andLuty, 1989, Fan et al, 2005;Sukla et al, 2006). Highly variable STR loci are common in mammalian genomes and can readily be typed by Polymerase Chain Reaction followed by electrophoresis on denaturing ureapolyacrylamide gel (Sodhi et al, 2006). These attributes make microsatellites the ideal marker to reveal parentage/genetic relationships between individuals.…”
Section: Introductionmentioning
confidence: 99%